An open study of valproate in subfertile men with epilepsy. (20th July 2020) - Markoula, Sofia; Siarava, Eleftheria; Kostoulas, Charilaos; Zikopoulos, Athanasios; Georgiou, Ioannis
Abstract : Objectives: The aim of the study was to assess whether, male patients with epilepsy, switching from valproic acid (VPA) to levetiracetam (LEV) or lamotrigine (LMG) critically improves sperm counts and parameters, increasing chance of patients' female partners to spontaneously conceive. Materials and methods: This is an observational prospective study recruiting all consecutive infertile male patients with epilepsy followed up at the outpatient Epilepsy Clinic of University Hospital of Ioannina, Northwest Greece. Infertile couples were referred to the Laboratory of Assisted Reproduction and Treatment of the University Hospital of Ioannina to conduct semen analysis. The first sample was collected while the patients were receiving VPA, and the second semen sample was collected after the patients were switched to LEV or LMG. Results: Seventeen infertile male patients were recruited in the study. Nine patients were switched to LEV, and eight patients were switched to LMG. The mean sperm count increased after VPA withdraw P  = .06. Motility was improved with an increase of total motility and non‐progressive motility ( P  = .02 and P  = .03, accordingly), whether sperm defects were decreased, mainly head defects ( P  = .03). Differences between patients switched to LEV or LMG were minimal and showed no significant findings. Spontaneous pregnancies were reported in three of the patients' partners, without any other clinical intervention offered to the couple. Conclusion: Switching from valproic acid to levetiracetam or lamotrigine improved sperm counts and other sperm parameters in subfertile male patients and increased the chance of spontaneously conceiving in subfertile couples.